Effect of polydopamine coating on adhesion of resin composite to polyetherketoneketone (PEKK) - Santos Diamantino, Pedro Jacy [UNESP]; Gimenez, Mariana Gadelho [UNESP]; Duarte, Lais; Phillippi, Analucia Gebler; Özcan, Mutlu; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP]; de Oliveira Barra, Guilherme Mariz; Gonçalves, Thais Marques Simek Vega (My University, 2023)
Statement of problem: Polydopamine (PD) adsorbs on all kinds of surfaces by forming strong covalent bonds, and develops cohesive strength through self-polymerization, resulting on thin strong adhesive films. Thus, PD coating could be promising to improve the adhesion to the inert Polyetherketoneketone (PEKK). Purpose: To analyze different protocols of PD coating to improve gingiva veneering resin composite bonding to PEKK. Material and methods: Milled PEKK specimens were fabricated and ultrasonically cleaned. Dopamine hydrochloride (Sigma Aldrich) was mixed with TRIS-HCl buffer (Sigma Aldrich) at pH 8.5 to obtain concentration of 1, 2, and 4 mg/mL. Each concentration was applied for 7 and 14 h to coating PEKK surface. Controls groups without treatment, surface treatment (with and without air abrasion), and bonding treatment (PEKKBond (AnaxDent)) were used for comparisons (n = 36 each). Morphological topography was analyzed, and flowable gingiva colored composite resin (AnaxGum, Anaxdent) were bonded to PEKK surface. Specimens were aged for 24 h (37 °C) and the shear bond strength (SBS) was assessed in universal test machine (MPa). Statistical analysis was performed by using 2-way ANOVA followed by Tukey's tests (α = 0.05). Results: All main effects and interactions were significant (P <.05). In general, PD coating reduced the adhesion between PEKK and veneering composite (P <.001), regardless of the concentration or the time of application (P >.05). The conventional adhesive (PEKKBond) presented the highest SBS values, regardless prior to air abrasion treatment. Conclusion: The PD coating of PEKK does not improve the bond strength between gingiva veneering composite and PEKK. Clinical implications: Surface conditioning of PEKK surface properties is of interest to the dental community and, therefore, many treatments have been suggested to increase the adhesiveness of such polymer. However, PD coating is not an efficient bonding agent for PEKK and should not be used in a clinical practice since it is time-consuming and reduces the adhesion to PEKK.